Developments in the life insurance industry in Jamaica 1990-1998 : consequences for monetary policy - Foga, Camille ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2000)
Discusses the evolution of the problems that emerged in the life insurance industry with a view to identifying the weaknesses that contributed to the problems in the industry. Explores the monetay policy implications of instability in this segment of the capital market. Focuses on the features of the legislative and supervisory framework that governed the industry, with particular emphasis on the weaknesses that conpanies were able to exploit.